Effectiveness of Awake Prone Position in Non-Intubated ARDS Patients: A Literature Review - Tan, Julianus Yudhistira; Kosasih, Cecep Eli; Mediani, Henny Suzana (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Background: The prone position is one of the highly recommended interventions to treat hypoxaemia and lung injury in ARDS patients. However, its efficacy in non-intubated patients remains inconclusive due to predominantly being reviewed through observational and case studies. This review aims to evaluate the efficacy of prone position on the oxygenation status and mortality rate of ARDS patients through experimental studies. Methode: This review systematically searched three international databases: PubMed, Web of Science, and CINAHL from November to December 2022, without restricting the publication year. The focus was solely on experimental studies examining the effectiveness of prone positioning in adult, non-intubated ARDS patients. The quality of studies was assessed using the JBI critical appraisal tool. Results: Of the 12 included studies, most RCTs were identified as poor quality. All patients appeared to be infected with Covid-19, and the majority were on conventional oxygen therapy. Most studies showed that the prone position was effective in improving the oxygenation status for up to two hours post-session, with a mortality rate not substantially different from that of control group. Further good-quality experimental studies are needed to strengthen these results. Conclusion: The prone position is quite effective in improving the oxygenation status of patients.